The study on cuproptosis in Alzheimer’s disease based on the cuproptosis key gene FDX1 - Chen, Guilin; Xi, Erwei; Gu, Xiaozhen; Wang, Huili; Tang, Qiqiang (Frontiers in Aging Neuroscience, 2024)
BackgroundAlzheimer’s disease (AD) is a neurodegenerative disorder characterized by memory and cognitive impairments. Previous studies have shown neuronal death in the brains of AD patients, but the role of cuproptosis and its associated genes in AD neurons remains unclear.MethodsIntersection analysis was conducted using the AD transcriptome dataset GSE63060, neuron dataset GSE147528, and reported cuproptosis-related genes to identify the cuproptosis key gene FDX1 highly expressed in AD. Subsequently, cell experiments were performed by treating SH-SY5Y cells with Aβ25-35 to establish AD cell model. The real-time reverse transcriptase-polymerase chain reaction (RT-qPCR) and western blotting (WB) assays were employed to detect the expression levels of FDX1, DLAT, and DLST. Cell proliferation was analyzed by counting Kit-8 (CCK8), mitochondrial ROS levels were analyzed using flow cytometry. shRNA was used to downregulate FDX1 expression, followed by repetition of the aforementioned experiments. Clinical experiments utilized qPCR to detect FDX1 mRNA levels in peripheral venous blood of patients, and analyzed FDX1 expression differences in different APOE genotypes of AD patients. Finally, a protein–protein interaction (PPI) network of FDX1 was constructed based on the GeneMANIA database, immune infiltration analysis was conducted using R language, and transcription factors prediction for FDX1 was performed based on the ENCODE database.ResultsThe cuproptosis key gene FDX1 showed significantly higher expression in peripheral blood and neuron models of AD compared to non-AD individuals, with significantly higher expression in APOE ε4/ε4 genotype than other APOE genotype of AD patients. Knockdown of FDX1 expression reduced the lipidation levels of DLAT and DLST in neurons, alleviated ROS accumulation in mitochondria, improved cell viability, and mitigated cuproptosis. Immune infiltration analysis results indicated a high enrichment of peripheral blood γδ-T lymphocytes in AD, and FDX1 was significantly associated with the infiltration of four immune cells and may be regulated by three transcription factors.ConclusionThe cuproptosis key gene FDX1 is highly expressed in AD and may promote cuproptosis in AD neurons by regulating the lipidation levels of DLAT and DLST, thereby participating in the onset and development of AD. This provides a potential target for the diagnosis and treatment of AD.